Exploring disparities in incidence and mortality rates of breast and gynecologic cancers according to the Human Development Index in the Pan-American region. (August 2017) - Martínez-Mesa, J.; Werutsky, G.; Michiels, S.; Pereira Filho, C.A.S.; Dueñas-González, A.; Zarba, J.J.; Mano, M.; Villarreal-Garza, C.; Gómez, H.; Barrios, C.H.
Abstract: Objective: To evaluate whether a country's Human Development Index (HDI) can help explain the differences in the country's breast cancer and gynecological cancer incidence and mortality rates in the Pan-American region. Study design: Ecological analysis. Methods: Pan-American region countries with publicly available data both in GLOBOCAN 2012 and the United Nations Development Report 2012 were included ( n = 28). Incidence and mortality rates age-standardized per 100, 000 were natural log-transformed for breast cancer, ovarian cancer, corpus uteri cancer, and cervical cancer. The mortality-to-incidence ratio (MIR) was calculated for each site. Pearson's correlation test and a simple linear regression were performed. Results: The HDI showed a positive correlation with breast cancer and ovarian cancer incidence and mortality rates, respectively, and a negative correlation with cervical cancer incidence and mortality rates. The HDI and corpus uteri cancer showed no association. MIR and the HDI showed a negative correlation for all tumor types except ovarian cancer. An increment in 1 HDI unit leads to changes in cancer rates: in breast cancer incidence β = 4.03 (95% confidence interval [CI] 2.61; 5.45) P < 0.001, breast cancer mortality β = 1.76 (95% CI 0.32; 3.21) P = 0.019, and breast cancer-MIR β = −0.705 (95% CI 0.704; 0.706) P < 0.001; in cervical cancer incidence β = −3.28 (95% CI −4.78; −1.78) P < 0.001, cervical cancer mortality β = −4.63 (95% CI −6.10; −3.17) P < 0.001, and cervical cancer-MIR β = −1.35 (95% CI −1.83; −0.87) P < 0.001; in ovarian cancer incidence β = 3.26 (95% CI 1.78; 4.75) P < 0.001, ovarian cancer mortality β = 1.82 (95% CI 0.44; 3.20) P = 0.012, and ovarian cancer-MIR β = 5.10 (95% CI 3.22; 6.97) P < 0.001; in corpus uteri cancer incidence β = 2.37 (95% CI −0.33; 5.06) P = 0.83, corpus uteri cancer mortality β = 0.68 (95% CI −2.68; 2.82) P = 0.96, and corpus uteri cancer-MIR β = −2.30 (95% CI −3.19; −1.40) P < 0.001. Conclusions: A country's HDI should be considered to understand disparities in breast cancer and gynecological cancer in the Pan-American region. Highlights: Differences in a country's Human Development Index (HDI) could explain inequities in breast cancer and gynecological cancer incidence and mortality rates. An increment in one HDI unit leads to increments in breast cancer and ovarian cancer incidence and mortality rates. An increment in one HDI unit leads to a decrease in cervical cancer incidence and mortality rates.